Struggling to Define a Nation : American Music and the Twentieth Century - Garrett, Charles Hiroshi, 1966- (Book collections on Project MUSE., 2008)
Identifying music as a vital site of cultural debate, this book captures the dynamic, contested nature of musical life in the United States. It examines an array of genres - including art music, jazz, popular song, ragtime, and Hawaiian music - and well-known musicians, such as Charles Ives, Jelly Roll Morton, Louis Armstrong, and Irving Berlin.